Hypertension in rural communities in Delta State, Nigeria: Prevalence, risk factors and barriers to health care - Mary I. Ofili; Busisiwe P. Ncama; Benn Sartorius (AOSIS, 2015)
Introduction: Hypertension is a global health challenge and its prevalence is increasing rapidly amongst adults in many African countries. Some studies on the prevalence and risk factors of hypertension have been conducted in Nigeria, but none within Delta State. We assessed the prevalence of hypertension and associated risk factors amongst adults in three villages in the Ibusa community in Delta State, Nigeria. Method: Homesteads were randomly selected and all consenting adults (≥ 18 years of age) were recruited for this cross-sectional study (134 individuals: 48 men, 86 women). Sociodemographic data and anthropometric measurements (weight, height and abdominal circumference) were recorded. Diagnosis of hypertension was based on blood pressure≥ 140/90 mmHg. Result: Hypertension prevalence in this rural community was 44%. Results from one village (Ogboli: 82%) and ethnic group (Ibo: 50%) were significantly higher than in others in the same variable category. Multivariate logistic regression analysis suggested increasing age, increasing body mass index and high salt intake as prominent risk factors for hypertension. Lack of funds and equipment shortage in clinics were most often reported as barriers to healthcare. Conclusion: A nutritional education programme to promote low-cholesterol and low-salt diets is recommended to specifically target people in higher-risk areas and of higher-risk ethnicity. Local barriers to accessing health care need to be addressed.